CLINICAL CASES OF ANALYZING OBSERVATIONS OF COMBINED CONGENITAL MALFORMATIONS OF THE BRAIN AND VISION IN NEWBORNS - Aziza Tahirovna Djurabekova; Umida Hamidovna Vaseyeva (Scholar Express Journals, 2024)
The present study is aimed at investigating clinical and diagnostic features of combined congenital malformations of the brain and vision in children
Keywords: Congenital Malformations; Brain; Vision